Analysis of genetic diversity of Sclerotinia sclerotiorum from eggplant by mycelial compatibility, random amplification of polymorphic DNA (RAPD) and simple sequence repeat (SSR) analyses - Fatih Mehmet Tok; Sibel Derviş; Mehmet Arslan (Biotechnology & Biotechnological Equipment, 2016)
The genetic diversity and pathogenicity/virulence among 60 eggplant Sclerotinia sclerotiorum isolates collected from six different geographic regions of Turkey were analysed using mycelial compatibility groupings (MCGs), random amplified polymorphic DNA (RAPD) and simple sequence repeat (SSR) polymorphism. By MCG tests, the isolates were classified into 22 groups. Out of 22 MCGs, 36% were represented each by a single isolate. The isolates showed great variability for virulence regardless of MCG and geographic origin. Based on the results of RAPD and SSR analyses, 60 S. sclerotiorum isolates representing 22 MCGs were grouped in 2 and 3 distinct clusters, respectively. Analyses using RAPD and SSR markers illustrated that cluster groupings or genetic distance of S. sclerotiorum populations from eggplant were not distinctly relative to the MCG, geographical origin and virulence diversity. The patterns obtained revealed a high heterogeneity of genetic composition and suggested the occurrence of clonal and sexual reproduction of S. sclerotiorum on eggplant in the areas surveyed.